Save or borrow: what determines Russian households' financial strategies? - Maria Semenova (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
We analyze the determinants of debt choices for Chinese firms between bonds and syndicated loans. This issue helps appraise the weak development of bond market in China. We test if flotation costs, asymmetries of information, and renegotiation and liquidation costs influence the choice of debt in line with former studies in the context of regulatory interference in the bond market. We check the role of central state ownership on debt choice in order to assess to what extent corporate debt choices are politically or economically driven. We test these hypotheses on a dataset of 220 listed Chinese firms over the period 2006 2010. We find evidence in favour of the influence of central government ownership on the financing choices of firms it owns, as central state-owned firms are more likely to issue bonds. We also observe limited support for the premise that this influence is stronger for central state-owned firms located closer to the capital. Furthermore, we identify that these companies tend to borrow uniquely on the bond market rather than tapping both debt markets. We provide evidence in favour of the flotation costs hypothesis, but provide mixed evidence for the information asymmetry hypothesis and rather reject the renegotiation and liquidation hypothesis. All in all, our findings show that financial factors play a much more minor role in corporate debt choices compared to other countries, whereas state ownership remain a key determinant of preferring the bond market.
URN:NBN:fi:bof-201408072183
Keywords: 330